2005
DOI: 10.1002/ddr.20006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intrasperm Ca2+: A possible maneuver for spermicidal activity

Abstract: Sperm in the testis and proximal part of epididymis are nonmotile. in sperm function and to critically evaluate the possible use of pharmacological agents as contact spermicides. This should aid in identifying novel target sites for arresting sperm viability in ejaculated human semen. As these agents will act on ejaculated sperm, they should be devoid of any adverse effects associated with the other contraceptives. The ideal agent will be one that acts selectively on a sperm Ca 21 mobilization process or prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 167 publications
0
6
0
Order By: Relevance
“…These studies revealed that an elevation of intrasperm [Ca 2þ ] to $1200 nM produced complete loss of viability of human ejaculated sperm cells. Hence, pharmacological modulation for achieving this critical intrasperm [Ca 2þ ] threshold seems to offer a feasible approach for contact spermicidal activity (Gupta et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that an elevation of intrasperm [Ca 2þ ] to $1200 nM produced complete loss of viability of human ejaculated sperm cells. Hence, pharmacological modulation for achieving this critical intrasperm [Ca 2þ ] threshold seems to offer a feasible approach for contact spermicidal activity (Gupta et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ and pH may in turn control the phosphorylation state of functional proteins in the flagellar axoneme activated directly through cAMP and cAMP-dependent kinase [140,141]. Therefore, each step in the calcium-mediated regulatory process could serve as a potential target site for spermicidal action [142]. To interrupt these steps using inhibitors or blocking agents could provide insight into the mechanisms of spermicidal action.…”
Section: Major Possible Pathways By Which the Spermicides Work Changementioning
confidence: 99%
“…In summary, while the potential contraceptive and microbicidal activity of acid buffers has been clearly demonstrated in vivo, it remains to be seen whether delivery systems can be developed capable of Calcium ions are involved in regulation of sperm motility. Decreased extracellular Ca 2+ and increased intracellular Ca 2+ are both detrimental to sperm motility [62]. CatSper1 is a gated cation channel that is essential for cAMP induced Ca 2+ influx into sperm [63].…”
Section: Regulation Of Ca 2+mentioning
confidence: 99%